FORMULASI GRANUL KOMBINASI EKSTRAK TERPURIFIKASI HERBA PEGAGAN (Centella asiatica (L.) Urban) DAN HERBA SAMBILOTO (Andrographis paniculata (Burm.f.) Nees) - , LINA WIDIYASTUTI, Prof. Dr. Suwidjiyo Pramono, DEA, Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The combination of pegagan herb (Centella asiatica ( L.) Urban) and sambiloto herbs (Andrographis paniculata (Burm. F ) Nees) purified extract has the effect on lowering blood glucose levels, hypercholesterolemia and hypertriglyceridemia. Formulation dosage form required to obtain an easily acceptable and meets the parameters quality of the drug. The research was aims to study produce combination of pegagan (Centella asiatica (L.) Urban) herb and sambiloto (Andrographis paniculata (Burm. f.) Nees) herb purified extract with physical properties that meet the requirements and release the active ingredient of the combination of Avicel PH 101 and PVP K -30 as well as how the composition of each factor to produce the optimum formula. The physical characteristics analyzed using factorial method with Design Expert. The determination profile and mechanism dissolution takes based on curve fitting the andrografolid cumulative weight regardless. Dissolution profile interpretation takes views visually suitability model built from the zero-order approximation, first-order, Higuchi, Hixon Crowell and Korsmeyer Peppas on line identity goodness of fit. Research results showed that combination of Avicel PH 101 and PVP K-30 as well as combinations of interactions can produce granules combination of pegagan (Centella asiatica (L.) Urban) herb and sambiloto (Andrographis paniculata (Burm. f.) Nees) herb purified extract with a flow rate of 11.50 ± 0.41 g/sec, absorption potency 26.58 ± 1.21 mg/minutes, moisture content 4.6% ± 0.21, tapping index 16.33% ± 0.58 and dissolution efficiency (DE60)75.0% ± 1.33. Optimum formula with weight combination of pegagan herb (Centella asiatica ( L.) Urban) and sambiloto herbs (Andrographis paniculata (Burm. F ) Nees) purified 360 mg, Avicel PH 101 360 mg and PVP K-30 18 mg resulted granules with physical properties that meet the requirements of the release profile of the active substance followed by the Fick law Korsmeyer Peppas model approach.